2005
DOI: 10.1590/s1415-43662005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Sistema computacional aplicado ao cálculo da demanda hídrica georeferenciada para a cultura do feijão

Abstract: Para se determinar as demandas de irrigação e as melhores datas para o plantio da cultura do feijoeiro na bacia dos Rios do Leste, implementou-se um programa computacional, denominado DEMANDAsis, que se baseia no balanço de água no solo, consistindo de um sistema composto por programas e bancos de dados. Os resultados sobre datas propícias ao plantio do feijão na bacia dos Rios do Leste indicaram que o período entre 5 e 19 de outubro é o que assegura maior disponibilidade de água de origem pluvial durante o ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…These values met crop water requirements during growing cycle found by some authors conducting experiments in Brazil (DANTAS NETO et al, 2005;NÓBREGA et al, 2001;SILVEIRA;. Additionally, Doorenbos and Kassam (2000) concluded that maximum bean yield is achieved when 300 to 400 mm is available during the cycle, depending on the local edaphoclimatic conditions.…”
Section: Rainfall and Irrigationsupporting
confidence: 63%
“…These values met crop water requirements during growing cycle found by some authors conducting experiments in Brazil (DANTAS NETO et al, 2005;NÓBREGA et al, 2001;SILVEIRA;. Additionally, Doorenbos and Kassam (2000) concluded that maximum bean yield is achieved when 300 to 400 mm is available during the cycle, depending on the local edaphoclimatic conditions.…”
Section: Rainfall and Irrigationsupporting
confidence: 63%